Countermeasures of Specimens Showing below Reference Value in APTT Result - Choi, Hyun Oh; Kim, Seung Gu; Park, Sang Hee; Lee, Jae Ki; Koo, Bon Kyung; Park, Chang Ho (Korean journal of clinical laboratory science, 2013)
The activated partial thromboplastin time (APTT) is used primarily to evaluate coagulation abnormalities in the intrinsic pathway. The proper specimen is very important factor for precise results of blood coagulation analysis. The objective of this study was to get to the conclusion of whether to analyze again and to collect blood sample over again when APTT result shows below the reference value. We evaluated 126 samples showing a value below 20.0 sec at ATPT result, which consist of 48 males and 78 females candidates during night duty from March 2012 to December 2012. Average comparisons of APTT result between first and retested analysis among study subjects were significantly different in male samples. APTT results comparison of recollected subjects among clotted samples were also significantly different with both sexes (p＜0.000). We suggest that we should carefully check the samples to get accurate results and collect samples again in case of only obtaining improper samples; even though the APTT result show below reference value.